Twin arginine translocation, ammonia incorporation, and polyamine biosynthesis are crucial for Proteus mirabilis fitness during bloodstream infection. - Chelsie E Armbruster; Valerie S Forsyth; Alexandra O Johnson; Sara N Smith; Ashley N White; Aimee L Brauer; Brian S Learman; Lili Zhao; Weisheng Wu; Mark T Anderson; Michael A Bachman; Harry L T Mobley (PLoS Pathogens, 2019)
The Gram-negative bacterium Proteus mirabilis is a common cause of catheter-associated urinary tract infections (CAUTI), which can progress to secondary bacteremia. While numerous studies have investigated experimental infection with P. mirabilis in the urinary tract, little is known about pathogenesis in the bloodstream. This study identifies the genes that are important for survival in the bloodstream using a whole-genome transposon insertion-site sequencing (Tn-Seq) approach. A library of 50,000 transposon mutants was utilized to assess the relative contribution of each non-essential gene in the P. mirabilis HI4320 genome to fitness in the livers and spleens of mice at 24 hours following tail vein inoculation compared to growth in RPMI, heat-inactivated (HI) naïve serum, and HI acute phase serum. 138 genes were identified as ex vivo fitness factors in serum, which were primarily involved in amino acid transport and metabolism, and 143 genes were identified as infection-specific in vivo fitness factors for both spleen and liver colonization. Infection-specific fitness factors included genes involved in twin arginine translocation, ammonia incorporation, and polyamine biosynthesis. Mutants in sixteen genes were constructed to validate both the ex vivo and in vivo results of the transposon screen, and 12/16 (75%) exhibited the predicted phenotype. Our studies indicate a role for the twin arginine translocation (tatAC) system in motility, translocation of potential virulence factors, and fitness within the bloodstream. We also demonstrate the interplay between two nitrogen assimilation pathways in the bloodstream, providing evidence that the GS-GOGAT system may be preferentially utilized. Furthermore, we show that a dual-function arginine decarboxylase (speA) is important for fitness within the bloodstream due to its role in putrescine biosynthesis rather than its contribution to maintenance of membrane potential. This study therefore provides insight into pathways needed for fitness within the bloodstream, which may guide strategies to reduce bacteremia-associated mortality.